2016
DOI: 10.1016/j.molonc.2016.05.002
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Hsp90‐binding immunophilin FKBP51 forms complexes with hTERT enhancing telomerase activity

Abstract: FKBP52 are the best characterized Hsp90-bound immunophilins first described associated to steroid-receptors. The reverse transcriptase subunit of telomerase, hTERT, is also an Hsp90 client-protein and is highly expressed in cancer cells, where it is required to compensate the loss of telomeric DNA after each successive cell division. Because FKBP51 is also a highly expressed protein in cancer tissues, we analyzed its potential association with hTERT$Hsp90 complexes and its possible biological role. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 81 publications
1
46
0
Order By: Relevance
“…FKBP51 promotes melanoma growth by modulating TGF‐β expression and activating NF‐κB, which induces interleukin‐8 (IL‐8) . Moreover, FKBP51 acts as an anti‐apoptotic factor in cancer development and progression by enhancing the telomerase activity of hTERT . FKBP51 controls androgen‐dependent growth of prostate cancer by enhancing activity of androgen receptor transcription .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FKBP51 promotes melanoma growth by modulating TGF‐β expression and activating NF‐κB, which induces interleukin‐8 (IL‐8) . Moreover, FKBP51 acts as an anti‐apoptotic factor in cancer development and progression by enhancing the telomerase activity of hTERT . FKBP51 controls androgen‐dependent growth of prostate cancer by enhancing activity of androgen receptor transcription .…”
mentioning
confidence: 99%
“…T he FK506 binding protein FKBP51 (also referred as FKBP5) is highly expressed in prostate cancer, lymphoma, and melanoma; furthermore, FKBP51 expression correlates with metastatic potential in melanoma and prostate cancer, and its silencing restores resistance to apoptosis in these two cancers. (1)(2)(3)(4)(5)(6)(7) FKBP51 promotes melanoma growth by modulating TGF-b expression and activating NF-jB, which induces interleukin-8 (IL-8). (3)(4)(5) Moreover, FKBP51 acts as an anti-apoptotic factor in cancer development and progression by enhancing the telomerase activity of hTERT.…”
mentioning
confidence: 99%
“…These can only strengthen the argument that FKBP52 could have an important role in DNA damage signalling and repair, possibly through the cochaperone mechanism that also appears in many different processes or possibly it could be through the activity of its PPIase domain, which stabilises and activates many proteins in the cell. hTERT (Lagadari, Zgajnar, Gallo, & Galigniana, 2016). The study found that both FKBP51 and FKBP52 co-immunoprecipitate with hTERT.…”
Section: Fkbp52 and Tauopathiesmentioning
confidence: 86%
“…The proposed mechanism infers that FKBP52 is required for the retro transport of hTERT through dynein/dynactin. Once inside the nucleus FKBP51 replaces FKBP52 and enhances hTERT activity (Lagadari et al, 2016). The hTERT transport mechanism was further elucidated by Jong et al, (2016) showing that FKBP52 is required for the interaction with the dynein-dynactin motor protein complex, and subsequent transport of hTERT into the nucleus.…”
Section: Fkbp52 and Tauopathiesmentioning
confidence: 99%
See 1 more Smart Citation